The ocean returns: Mapping a mercurial Anthropocean. (September 2018) - Probyn, Elspeth
Humans have dumped 'stuff' in oceans in a particularly concentrated way since the Industrial Revolution, the effects of which we now note as evidence of the Anthropocene – or the Anthropocean. In this article, I consider what the oceans now return to us in the form of pollution. I trace the production of a mercurial ocean through the production of mercury as it is taken up and transported by atmospheric and oceanic currents from artisanal mines in Asia, and transformed into methylmercury. As methylmercury, it enters into the food chain and eventuates in the diets of certain populations, especially those in Nordic countries, with toxic effects into future generations. This, I argue, produces a particular ocean, one with temporal and spatial multiplicity. The flow of mercury is gendered and racialized with women workers in Indonesia being primarily affected while women in the north are the recipients of methylmercury in the form of toxic fish. I engage with scientific research on mercury flows and methylmercury biogeochemical cycling, and draw on the work of Annemarie Mol on the body multiple, feminist research into epigenetics (Mansfield, Guthman, Landecker), and feminist environmental posthumanism (Alaimo, Neimanis). My argument seeks to disturb the singular and othered ocean in order to make way for the ocean multiple – a conception of the different forms of the oceanic produced through the athwart admixtures of the more-than-human (Helmreich, Probyn).